2006
DOI: 10.1158/1535-7163.mct-05-0334
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal progenitor cells as cellular vehicles for delivery of oncolytic adenoviruses

Abstract: Natural and genetically modified oncolytic viruses have been systematically tested as anticancer therapeutics. Among this group, conditionally replicative adenoviruses have been developed for a broad range of tumors with a rapid transition to clinical settings. Unfortunately, clinical trials have shown limited antitumor efficacy partly due to insufficient viral delivery to tumor sites. We investigated the possibility of using mesenchymal progenitor cells (MPC) as virus carriers based on the documented tumorhom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
226
2
9

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(242 citation statements)
references
References 42 publications
5
226
2
9
Order By: Relevance
“…Les CSM ont également été utilisées pour apporter au site de la tumeur des molécules stimulant la réponse immunitaire telles que l'interleukine-12 (IL-12) [27] ou l'interféron gamma (IFN-) [28]. Enfin, les CSM ont aussi été utilisées comme vecteurs de virus oncolytiques au site tumoral, une stratégie particulièrement efficace dans le cas du cancer de l'ovaire [29] (voir aussi [33])…”
Section: Les Csm : Véhicules Pour Une Thérapie Cellulaire Antitumoraleunclassified
“…Les CSM ont également été utilisées pour apporter au site de la tumeur des molécules stimulant la réponse immunitaire telles que l'interleukine-12 (IL-12) [27] ou l'interféron gamma (IFN-) [28]. Enfin, les CSM ont aussi été utilisées comme vecteurs de virus oncolytiques au site tumoral, une stratégie particulièrement efficace dans le cas du cancer de l'ovaire [29] (voir aussi [33])…”
Section: Les Csm : Véhicules Pour Une Thérapie Cellulaire Antitumoraleunclassified
“…An assortment of cells have been explored in this regard, including tumor cells, [49][50][51][52] outgrowth endothelial cells, 53 mesenchymal progenitor cells, 54,55 T cells 56,57 and monocytes. 58 There are several criteria that need to be addressed when determining which cell type should be utilized as a carrier for the delivery of a given oncolytic virus: (i) susceptibility to oncolytic virus infection, (ii) protection of the cargo from antibody neutralization, (iii) homing to sites of tumor growth and (iv) transfer of virus progeny to tumor tissue.…”
Section: Utilization Of Cell Carriers To Circumvent Virotherapy Barriersmentioning
confidence: 99%
“…59,60 One study has shown that adenovirus-infected MPCs have tumorhoming capabilities after local or systemic administration. 54,55 A major advantage of MPCs is that they are readily available from healthy donors and can be expanded quickly in cell culture. 61 Therefore, it can be suggested that MPCs have the potential to serve as cell carriers for the treatment of MM, since these cells are derived from the bone marrow and travel via the blood vessels.…”
Section: Mesenchymal Progenitor Cellsmentioning
confidence: 99%
“…A fascinating possibility would be, prior to OV/carrier treatment, to begin by injecting cells known to respond to chemotactic molecules and growth factors produced by tumours (for example mesenchymal, endothelial or bone marrow progenitors). [48][49][50][51][52] The natural or built-in chemoresistance of these cells should enhance their participation in tumour vessel formation in patients under chemotherapy. 53 By administering such Trojan horses at the time of primary tumour resection, which often correlates with the release of metastatic growth from anti-angiogenic restrictions, 54 it should be possible to promote their infiltration into the pre-metastatic niche.…”
Section: Use Of Combination Strategies To Improve Carrier Cell-mediatmentioning
confidence: 99%